PENGARUH MOTIVASI KERJA, MANAJEMEN TEKNOLOGI INFORMASI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH MENENGAH TINGKAT ATAS NEGERI DI KABUPATEN KULON PROGO (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The Influence of Working Motivation, Information Technology Management and Principal’s Leadership on the Teacher’s Performance at Public Senior High Schools at Kulon Progo regencyThis study aims to determine : a) the influence of working motivation Management of Information Technology and Principal’s Leadership on the teacher’s performance, b) the influence of the working motivation on the teacher’s performance, c) the influence of information tecnology management on the teacher’s performance, d) the influence of principal’s leadership on the teacher’s performance. The study was conducted in Kulon Progo regency, in the academic year of 2013. This research is a quantitative one using survey method. The population of this research is 380 public senior high school teachers in Kulon Progo regency. This reserach was sample taken 177 teachers by using accidental sampling techniques. The data in this result wascollected by using questionnaries. The data were analized by using multiple regression with three predictors. Mayor hypothesis testing used multiple regression analysis, and then individual hypothesis testing done by using partial corelation. The data processing used SPSS program V.16.0. All effective contribution was taken from the analysis result of the value of the determinat coefficient multiplied by 100 % and the effective contribution partially by multiplying the value of the Standardized Beta Coefficients with Zero–oder correlations value multiplied by 100 % for each independent variable.The results of the research show that the working motivation, information tecnology management and principal’s leadership simultanously have very positive and significant influence on the teacher’s performance. Effective contribution all together is 37,44 %. Effetive contribution individually of : a). working motivation has positive influence to the teacher’s performance is 7,55 %. b). Information technology management has positive influence to the teacher’s performance is 22,85 %, and c). Principal’s leadership has positive influence the teacher’s performance the effective contribution is 7,04 %.